Formation mechanism of stable NbC carbide phase in Nb-1Zr-0.1C (wt.%) alloy. (1st February 2018) - Vishwanadh, B.; Arya, A.; Tewari, R.; Dey, G.K.
Abstract: In the present work, several long standing issues related to the formation of various carbides and transformation of Nb2 C→NbC carbide in Nb-1Zr-0.1C alloy have been addressed. For this purpose, samples were processed by two routes. In the first route, as-solidified samples were extruded and recrystallized and in the second route, as-solidified samples were directly heat treated without imparting deformation. By combining detailed diffraction analyses and ab-initio calculations, identity of the Nb2 C carbides in the as-solidified and extruded samples, among the various reported Nb2 C crystal structures has been established as an orthorhombic crystal structure (α-Nb2 C) having Pnma space group. Chemical analyses showed that the Nb2 C carbides in extruded samples had higher Zr content as compared to the carbides formed in as-solidified samples. Experimental and theoretical results revealed that Zr destabilizes Nb2 C phase which was shown as a possible reason for the precipitation of a more stable (Nb, Zr)C phase in recrystallized as well as in directly heat treated as-solidified samples. Detailed precession electron diffraction analysis of (Nb, Zr)C particles showed that if the nucleation of precipitates occurs prior to recrystallization and the growth of the precipitates occurs simultaneously with recrystallization, precipitates do not exhibit specific orientation relationship (OR) with the matrix phase. In contrast, if nucleation and growth of precipitates take place after recrystallization or in samples which do not undergo recrystallization, a specific (Baker-Nutting) OR is followed. Finally, by establishing atomic interrelationship by high resolution electron microscopy, the formation mechanisms of (Nb, Zr)C carbides in different morphologies in Nb alloy have been explained. Graphical abstract: Image 1